(untitled) (Scottish Archaeological Internet Reports, 2009)
Together the dates provide an interesting sequence of human activity from the most distant human past of the area, into recent times. There is an obvious weakness in the lack of detailed information from many sites, but even the small amount of information available extends our knowledge of the area considerably. More importantly they provide a sound data base which is now available to be picked up by specialists who wish to increase knowledge of any one of several periods.